Online Cheating di Pendidikan Akuntansi dan Bisnis: Peran Dark Triad dan Locus of Control - Nelvina Margery; Nelsi Cerdik Intani Bate’e; Gracia Maharani Sepang; Tan Ming Kuang (Politeknik Ganesha Medan, 2025)
The rapid growth of digital learning has reshaped the academic landscape, but it has also raised serious concerns regarding academic integrity. One of the emerging issues is the increasing prevalence of online cheating, which may be influenced by students’ psychological traits. This study aims to examine the impact of psychopathy—one of the traits within the Dark Triad—on online cheating behavior, while also evaluating the moderating role of locus of control (LoC). The novelty of this research lies in its integration of Dark Triad personality traits (specifically psychopathy) and locus of control in understanding online cheating within accounting and business education. A quantitative approach was employed, using primary data collected through a structured questionnaire distributed to 208 university students in Indonesia. The sample was selected using purposive sampling, focusing on students majoring in accounting and business. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software.The findings reveal that: (1) psychopathy has a significant and positive influence on the tendency to engage in online cheating; (2) students with an external locus of control are more likely to exhibit dishonest behavior; however, (3) locus of control does not significantly moderate the relationship between psychopathy and online cheating. These results suggest that while personality traits and perceived control play important roles in shaping unethical behavior in digital learning environments, their interaction may not always be statistically significant. The study underscores the importance of addressing individual psychological factors and calls for integrative strategies—such as digital ethics education and moral reflection—to foster academic honesty in online settings, particularly within accounting and business education.